Breast intraductal papilloma as cause of bloody nipple discharge in a 2-year-old girl. Issue 1 (February 2015) - Capasso, R.; Mamone, R.; Rossi, E.; Zeccolini, M.; Rotondo, A.
Abstract Breast papillary lesion are an uncommon cause of bloody nipple discharge in children representing a great diagnostic and management challenge. In the present case, breast ultrasound examination, also by 3D and tomographic mode imaging, clearly identified and depicted the papillary lesion, not appreciable at physical examination, causing bloody nipple discharge in a 2-year-old girl. Given the risks of deformity to the developing gland, tissue fragmentation and under-sampling of papillary breast lesions related to biopsy, breast ultrasound evaluation is crucial in determining between conservative or invasive therapeutic approach.